Oral Health in the State of Kuwait: An Appraisal - Huda Nazar; Sabiha Al-Mutawa; Ahmad Abdul Rahman Asad; Jitendra Ariga; Ahmad AlSahli; Jagan Kumar Baskaradoss (Elsevier, 2024)
Background: Oral health issues have received significant attention from most global health agencies, which have integrated these issues into their noncommunicable disease, sustainable development, and universal health coverage objectives. Methods: This paper provides an update on the progress made in the last 2 decades and aims to highlight some of the challenges faced by the oral health care system in Kuwait. Results: Despite the nation's rising expenditure on oral health care, the prevalence of oral diseases remains high in Kuwait. The lack of reliable data on periodontitis and edentulism limits the ability of researchers to comment on the trends of these conditions. This emphasises the critical need for a nationwide household-level oral health survey in both pediatric and adult populations that would provide valuable information on the oral health status of these populations. Conclusion: In the future, Kuwait must invest more in oral disease prevention programs, especially among children and the high-risk communities of the population.